PENGARUH PROFITABILITAS DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN DIVIDEN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015- 2019) - Teguh Erawati; Diah Dwi Astuti (Fakultas Ekonomi UNIBBA, 2021)
This study aims to test empirically the effect of profitability and managerial ownership on dividend policy with firm size as a moderating variable. The population in this study are manufacturing sector companies listed on the Indonesia Stock Exchange (BEI) in 2015-2019. The research sample consisted of 11 companies after the elimination by purposive sampling method. This study uses secondary data in the form of company annual financial reports which are downloaded from www.idx.co.id . The analysis model uses multiple regression analysis to test the profitability and managerial ownership to dividend policy and model the absolute difference test analysis to test the moderating variable of firm size. The results of this study indicate that profitability has no effect on dividend policy and managerial ownership positive affects dividend policy, whereas firm size weakens the relationship between profitability against dividend policy and firm size weakens the relationship between managerial ownership against dividend policy